2022
DOI: 10.3390/ijerph19148277
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Pain-Induced Disability in German Women with Endometriosis during the COVID-19 Pandemic

Abstract: (1) Background: The main aim of this research was to examine the factors leading to pain-induced disability by assessing the impact of demographic, endometriosis-specific, pandemic-specific, and mental health factors. (2) Methods: Women with endometriosis who attended online support groups were invited to respond to an online survey during the first wave of the COVID-19 pandemic in Germany. The Pain Disability Index (PDI) was employed to assess disability-related daily functioning. Independent predictors of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…A large European survey revealed that 21% of study participants reported being diagnosed with depression as a result of a chronic pain disorder [ 11 ]. Depressive symptoms seem to play a major role in modifying the experiences and subsequent social and functional consequences of women with endometriosis [ 4 ]. Pain and depression might influence each other´s treatment, as has been shown in German patients with rheumatoid arthritis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large European survey revealed that 21% of study participants reported being diagnosed with depression as a result of a chronic pain disorder [ 11 ]. Depressive symptoms seem to play a major role in modifying the experiences and subsequent social and functional consequences of women with endometriosis [ 4 ]. Pain and depression might influence each other´s treatment, as has been shown in German patients with rheumatoid arthritis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…After initial diagnosis via laparoscopy and excision of the endometriotic lesions, pain persistence or recurrence is experienced by many patients [ 2 , 3 ]. The multidimensional chronic pain experience may lead to pain-induced disability in almost all areas of daily life [ 4 ]. As a result of the long diagnostic delay [ 5 ], women with endometriosis frequently use analgesics in order to mitigate pain and pain-induced disability long before the actual diagnosis, as well as after initial or recurrent surgical or hormonal therapy [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, three published papers appear J.I. Spencer 1,2 , G. MezquIta 1 , F. ShakIr 1 to have analysed results from the same survey (Schwab et al,2021;Schwab et al, 2022a;Schwab et al,2022b). One mid-2020 case-control study in 1,027 patients in Iran showed no change in Covid-19 infection in endometriosis patients (Moazzami et al, 2021), whilst another smaller case-control study of 401 patients in Italy conducted between March 2020 and April 2021 showed a slight increase in number of infections in endometriosis patients (Barretta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There are only 14 published studies examining the effects of Covid-19 on endometriosis patients ( Arena et al, 2021 ; Armour et al, 2022 ; Ashkenazi et al, 2022 ; Barretta et al, 2022 ; Demetriou et al, 2021 ; Evans et al, 2021 ; Moazzami et al, 2021 ; Nicolás et al, 2022 ; Rosielle et al, 2021 ; Schwab et al, 2021 ; Schwab et al, 2022a ; Schwab et al, 2022b ; Uccella et al, 2021 ; Yalçın Bahat et al, 2020 ). Of these, three published papers appear to have analysed results from the same survey ( Schwab et al, 2021 ; Schwab et al, 2022a ; Schwab et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation